Legal Implications of the Omnibus Law on Job Creation for the Protection of Informal Sector Workers in Metropolitan Cities in Indonesia - Pratama, Andi; Rahmawati, Siti (Generasi Sains Indonesia, 2025)
This study examines the legal implications of the Omnibus Law on Job Creation for the protection of informal sector workers in metropolitan Indonesia. While the law was introduced to simplify regulations, attract investment, and expand labor protections through universal access to social security schemes, its effectiveness for informal workers remains questionable. Drawing on legal analysis and a review of early implementation in urban contexts, the study finds that reforms emphasizing flexibility and deregulation tend to normalize precarious work arrangements rather than reduce them. The lack of explicit legal recognition for informal employment further perpetuates exclusion, limiting workers’ access to rights such as collective bargaining and dispute resolution. At the same time, the law’s mandate for universal social security represents a potential avenue for inclusion, though practical barriers such as irregular income and weak enforcement constrain its impact. The findings highlight a fundamental tension between economic growth and labor protection, underscoring the need for complementary local policies that address the realities of metropolitan informal economies.